Legal Pluralism in Aceh: Dynamics and Conflicts between Customary Law, Islamic Sharia, and National Law - Nur Ahmadi Akmal; Khairul Habibi (Islamic Studies and Civilization Journal, 2026)
This study analyses the dynamics and conflicts of legal pluralism in Aceh through three problem formulations: How are the dynamics of the relationship between the three legal systems, what are the points of conflict that arise, what are the mechanisms for resolving normative conflicts. The study uses a qualitative library research method with a sociology of law approach, analysing laws and regulations, Qanun, and academic literature using the legal pluralism theoretical framework of Griffiths and the semi-autonomous social field concept of Moore. The results show: The three systems interact through patterns of accommodation, negotiation, and competition with a formal hierarchy but more complex practices; Conflict occurs at three levels—normative, institutional, and implementation; Conflict resolution is carried out through formal and informal mechanisms. The limitations of the study are the absence of primary data from the field and a limited focus on the normative-theoretical aspects.